2015
DOI: 10.1016/j.jneumeth.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Near-field electromagnetic holography for high-resolution analysis of network interactions in neuronal tissue

Abstract: HighlightsWe developed a method to estimate electromagnetic field vectors from microelectrode array data.The vectors allow high-resolution holographic reconstruction of spatiotemporal activity.Separation of electromagnetic source density and dissipation informs on activity structure.Electromagnetic flow maps quantify dynamic causal interactions in brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Moreover, although surface‐plasmons are by definition near‐field waves, the desire to control the near‐field properties of other types of waves has drawn considerable attention in recent years. For example, shaping the nonlinear near‐file emitted from nanostructures , near‐field nonlinear on‐axis and volume holography at the second harmonic , acoustic near‐field holography , microwave near‐field holography , and more . The methods and approaches presented in this manuscript may be of interest and applications to these waves, and others, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although surface‐plasmons are by definition near‐field waves, the desire to control the near‐field properties of other types of waves has drawn considerable attention in recent years. For example, shaping the nonlinear near‐file emitted from nanostructures , near‐field nonlinear on‐axis and volume holography at the second harmonic , acoustic near‐field holography , microwave near‐field holography , and more . The methods and approaches presented in this manuscript may be of interest and applications to these waves, and others, as well.…”
Section: Discussionmentioning
confidence: 99%
“…This is possible thanks to the simultaneous decomposition of all dimensions of the data, which ensures the same number of IMFs containing the information in the same frequency ranges (Rehman and Mandic, 2010 ). Thus, thanks to the advantages of EMD algorithms over classic linear analysis, they are being increasingly used in neuronal analysis (Liang et al, 2005 ; Huang et al, 2013 ; Al-Subari et al, 2015 ; Alegre-Cortés et al, 2016 ), and they are helping us to achieve a better understanding of the oscillatory properties of neuronal activity (Buzsáki and Draguhn, 2004 ).…”
Section: Synergy Between Emds Machine Learning and Brain Processesmentioning
confidence: 99%
“…To facilitate the analysis of relevant T–F information using ML analysis, we propose to use Empirical Mode Decomposition data-driven algorithms (Huang et al, 1998 , EMD) to extract the relevant T–F features to be studied. This procedure is widely used in signal analysis and has been proved successfully in the analysis of electrophysiological data (Li, 2006 ; Huang et al, 2013 ; Hu and Liang, 2014 ; Al-Subari et al, 2015 ; Alegre-Cortés et al, 2016 ); nevertheless, they have not yet become of common use and are sparsely found in neuroscience publications. As a result, we still use linear and stationary techniques that are unavoidably biasing and blurring relevant information, since they are not able to accurately depict the intermittency and non-linearity of the data.…”
Section: Introductionmentioning
confidence: 99%